Creation of glyphosate-resistant Brassica napus L. plants expressing DesC desaturase of cyanobacterium Synechococcus vulcanus - Sakhno, L.O.; Gerasymenko, I.M.; Komarnitsskii, I.K.; Sheludko, Y.V.; Goldenkova-Pavlova, I.V. (Вiopolymers and Cell, 2012)
Aim. Creation of glyphosate-resistant canola plants expressing bifunctional hybrid desC::licBM3 gene. In the
hybrid gene the sequence of DesC desaturase of cyanobacterium S. vulcanus without plastid targeting was fused
with the sequence of thermostable lichenase reporter LicBM3 gene. Methods. Agrobacterium tumefaciensmediated transformation, PCR, quantitative and qualitative determination of lichenase activity, genetic
analysis. Results. Transgenic canola plants, carring the enolpyruvat shikimat phosphate syntase gene (epsps),
conferring on plants resistance to phosphonomethyl glycine herbicides (Roundup), as well as the desC::licBM3
gene, were selected. The presence of transgenes was confimed by multiplex PCR. The epsps gene expression in
canola was shown at the transcription level, during in vitro growth and after greenhouse herbicide treatment.
Activity of the licBM3 gene product as a part of hybrid protein allowed quantitative and qualiative estimation of
the desaturase gene expression. Inheritance of heterologous genes and their expression in the first generation
were investigated. Conclusions. Transgenic canola plants were obtained, the presence of trangenes in plant
genome was proved and expression of the target genes was detected.
Keywords: Brassica napus, desC, epsps, licBM3, lichenase. Цель. Создание растений рапса, устойчивых к глифосату и экспрессирующих бифункциональный гибридный ген desC::licBM3, в котором последовательность десатуразы DesC цианобактерии S. vulcanus без сигнала транспорта в пластиды слита с последовательностью гена репортерного белка термостабильной лихеназы LicB Clostridium thermocellum. Методы. Agrobacterium tumefaciens-опосредованная трансформация, ПЦР, качественное и количественное определение активности термостабильной лихеназы, генетический анализ. Результаты. Получены трансгенные растения рапса, несущие два целевых гена: енолпируватшикиматфосфатсинтазы (epsps), обеспечивающего устойчивость растений к гербицидам на основе фосфонометилглицина, и гена desC::licBM3. Присутствие трансгенов в геноме растений доказано методом мультиплексной ПЦР. Экспрессия гена epsps показана на уровне транскрипции, в условиях in vitro и in vivo (теплицa). Наличие продукта гена licBM3 в составе гибридного белка позволило оценить экспрессию слитого с ним гена десатуразы. Прослежено наследование введенных генов и их экспрессия в первом поколении. Выводы. Получены линии трансгенных растений рапса, подтверждено присутствие трансгенов в геноме растений и доказана экспрессия целевых генов.
Ключевые слова: Brassica napus, epsps, desC, licBM3, лихеназа. Мета. Створення стійких до гербіциду Roundup рослин ріпаку, що експресують біфункціональний гібридний ген desC::licBM3, в якому послідовність десатурази DesC ціанобактерії S. vulcanus без сигналу транспорту в пластиди злита з послідовністю гена репортерного білка ліхенази LicBM3 Clostridium thermocellum. Методи. Agrobacterium tumefaciens-опосередкована трансформація, ПЛР, якісне і кількісне визначення активності термостабільної ліхенази, генетичний аналіз. Результати. Отримано трансгенні рослини ріпаку, які несуть два цільових гени: єнолпіруватшикі- матфосфатсинтази (epsps), що забезпечує стійкість рослин до гербіцидів на основі фосфонометилгліцину, і гена desC::licBM3. Присутність трансгенів у геномі рослин підтверджено методом мультиплексної ПЛР. Експресію гена epsps показано на рівні транскрипціі, за умов in vitro та in vivo (теплиця). Наявність продукту гена licBM3 у складі гібридного білка дозволила оцінити експресію злитого з ним гена десатурази. Простежено успадкування введених генів і їхня експресія в першому поколінні. Висновки. Отримано лінії трансгенних рослин ріпаку, підтверджено присутність трансгенів у геномі рослин і доведено експресію цільових генів.
Ключові слова: Brassica napus, epsps, desC, licBM3, ліхеназа.